Expert Tracking And Maintenance System - Rabiu Nizam, Hasanabar Ali (2002)

(untitled)
The purpose of this project is to generate a Web-based database system model for medium-size organizations to improve the efficiency and effectiveness of the organization's functions. The Unified Approach methodology is used and model has been developed using the Unified Modeling Language (UML). A prototype system named Expert Tracking and Management System has also been developed. The MySQL Database, PHP Server-side scripting language and Apache web server are used to develop the System. The system model is defined to acts as a reference model of the organization's Tracking and management system. Some problems and limitations that were discovered during the development of project are discussed. Finally some recommendations to overcome the limitations for the future development of this project are presented.